Development of tunable multi beam antenna for High Altitude Platform Station (HAPS) – Progress II - Mohd Fareq, Abd Malek, Dr.; Soh, Ping Jack; Muhammad Ezanuddin, Abdul Aziz (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Kampus Pauh Putra, Arau, Perlis, Malaysia.